Virtual reality distraction: A novel behaviour management technique - Madhura Pawar; Parth Pandya; C Mendonca Rimple; Kinjalk Agrawal; Rupak Kumar Dasarraju; Shrinidhi Jain (Wolters Kluwer Medknow Publications, 2024)
Virtual reality distraction (VRD) is developing technologies for behavior management that can assist a child in adjusting to the dental setting and provide high-quality dental care. The purpose of this literature is to shed light on VRD and its application to the treatment of pediatric dental patients.